Research competence and formative research in preservice teacher education - Marta Sabariego Puig; Ana Belen Cano Hila; Begoña Gros Salvat; Begoña Piqué Simón (Universidad de La Rioja, 2020)
The present work is the result of a research project with the purpose of developing the research competence in the students of the Early Childhood Degree of the University of Barcelona (UB). This article describes the innovative experience developed in dual training environments, through formative research with 46 students in the Early Childhood Education Degree of the University of Barcelona. It details the design process and its phases, the contents worked, and the results obtained in the students' learning process. It confirms the development of research skills associated with initial training such as autonomy, search for information and creativity in project research to respond to identified problem situations; also, the development of cross-disciplinary skills, critical thinking and teamwork, as well as skills for the transfer and communication of knowledge.